Enrichment of soap formation from fruit extraction / Nor Fadilah Mohamad ... [et al.] - Mohamad, Nor Fadilah; Onn, Munirah; Alisha, Ain; Nadira, Nur; Salim, Aiman
In this study, three fruit waste had been used and tested to enrich the quality of soap. Some of improvements were recorded such as foaming ability, moisture content and solubility time to dissolve the soap. Only non-edible parts of the fruits were used in this study. It proves that this study is not only to enrich the soap, but it also can help to improve the waste utilization for a better recovery of the fruit waste. This study was done by crushing dried papaya seeds, pitaya peels and orange peels. The finding result from this study can be beneficial towards the human personal care and also for getting high potential of the thought on environmental guidance. Currently, over 23000 waste was generated each day in Malaysia The soap from fruit extraction have more benefits as it comes from natural sources and does not use hazardous chemical that can have adverse effects to human health.